2010
DOI: 10.1002/jcla.20395
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of serum interleukin 6 (IL‐6) and C‐reactive protein (CRP) in the differentiation between pancreatic cancer and chronic pancreatitis

Abstract: Previous studies have shown elevated serum levels of interleukin 6 (IL-6) and C-reactive protein (CRP) in patients with pancreatic cancer (PC). The aim of this study was to assess the diagnostic usefulness of pretreatment serum levels of IL-6 and CRP to differentiate between PC and chronic pancreatitis (CP) patients. Serum levels of CRP, IL-6, carcinoembryonic antigen (CEA), and carbohydrate antigen 19-9 (CA 19-9) were determined in 78 patients with PC before surgery, in 45 patients with CP, and in 70 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
83
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 20 publications
16
83
2
Order By: Relevance
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 59%
“…In the present study, we found that levels of the serum marker of acute inflammation (CRP) and an inflammatory mediator (TNFSF13) were significantly higher in patients with PDAC-DM than in those without diabetes and in pancreatitis patients. Though the serum levels of CRP and TNFSF13 in patients with PDAC-DM were not directly compared with those of healthy individuals in our study, the serum CRP and TNFSF13 levels in patients with chronic pancreatitis were shown to be slightly higher and the same as those of healthy individuals, respectively [18][19][20]. Our data demonstrated similar levels of CRP mRNA expression in tissues from patients with and without PDAC-DM, and in patients with chronic pancreatitis, excluding the possibility that PDAC lesions are the source of the elevated CRP in the serum of patients with PDAC-DM.…”
Section: Discussioncontrasting
confidence: 59%
“…It has been shown that serum IL-6 and CRP levels may be useful in the differentiation between diagnosis of pancreatic cancer and chronic pancreatitis (22). Kim et al reported that preoperative serum IL-6 and CRP levels may be markers of tumor invasion, lymph node metastasis and TNM stage (23).…”
Section: Discussionmentioning
confidence: 99%
“…The inding that IL-6 induces neutrophil apoptosis contributes to the resolution of acute neutrophil iniltration. Increased IL-6 level is often a beter predictor of disease activity in the context of infection, autoimmunity or cancer than C-reactive protein [24,25]. Consistent with the early description of IL-6 as a lymphocyte-stimulating factor, IL-6 deiciency leads to impaired innate and adaptive immunity to viral, parasitic and bacterial infection.…”
Section: Production and Medical Use Of Interleukin 6 (Il-6)mentioning
confidence: 79%